Instantaneous position and orientation of the body segments as an arbitrary object in 3D space by merging gyroscope and accelerometer information - Barraza-Madrgial, J. A.; Muñoz-Guerrero, R.; Lejia-Salas, L.; Ranta, R. (Revista Mexicana de Ingenieria Biomedica, 2014)
This work presents an algorithm to determine instantaneous orientation of an object in 3D space. The orientation was determined by using a Direction Cosine Matrix (DCM), performed by the combination of three consecutive rotations, around each to the main axes of the evaluated system, using quaternions. An inertial measurement unit (IMU), consisting of 3 axes gyroscope and 3 axes accelerometer was used in order to establish 2 coordinate systems; The first one describes object movement, by using gyroscope as a main source of information, relating the angular rate of change along time. The second defines a coordinate reference system, relating the acceleration of gravity to an inertial direction vector. A proportional integral (PI) feedback controller was used, which includes sensors information, eliminating offset, canceling drift and improving the accuracy of the orientation. The proposed algorithm can be used for assessing both the position and orientation of the body segments which is very important in orthopedic, traumatology and rheumatology important for diagnosis, prognostic, therapeutic, research and as well as the design and fabrication of measuring devices used in surgical instrumentation, prostheses and orthoses. It is important to note that the developed system opens the opportunities to be implemented on ambulatory joint evaluation through a wearable system, due to the dimensions and requirements of the sensors.